Supplementary movies to PhD thesis “Geometry-driven self-organization of migrating cells and chiral filaments” - Dunajova, Zuzana
These files contain supplementary movies accompanying the PhD thesis “Geometry-driven self-organization of migrating cells and chiral filaments” by Zuzana Dunajova (2026). The videos provide additional visual material supporting the experiments and results described in the thesis.

Dual role of FOXG1 in regulating gliogenesis in the developing neocortex via the FGF signalling pathway - Bose, Mahima; Suresh, Varun; Mishra, Urvi; Talwar, Ishita; Yadav, Anuradha; Biswas, Shiona; Hippenmeyer, Simon; Tole, Shubha (eLife)
In the developing vertebrate central nervous system, neurons and glia typically arise sequentially from common progenitors. Here, we report that the transcription factor Forkhead Box G1 (Foxg1) regulates gliogenesis in the mouse neocortex via distinct cell-autonomous roles in progenitors and postmitotic neurons that regulate different aspects of the gliogenic FGF signalling pathway. We demonstrate that loss of Foxg1 in cortical progenitors at neurogenic stages causes premature astrogliogenesis. We identify a novel FOXG1 target, the pro-gliogenic FGF pathway component Fgfr3, which is suppressed by FOXG1 cell-autonomously to maintain neurogenesis. Furthermore, FOXG1 can also suppress premature astrogliogenesis triggered by the augmentation of FGF signalling. We identify a second novel function of FOXG1 in regulating the expression of gliogenic cues in newborn neocortical upper-layer neurons. Loss of FOXG1 in postmitotic neurons non-autonomously enhances gliogenesis in the progenitors via FGF signalling. These results fit well with the model that newborn neurons secrete cues that trigger progenitors to produce the next wave of cell types, astrocytes. If FGF signalling is attenuated in Foxg1 null progenitors, they progress to oligodendrocyte production. Therefore, loss of FOXG1 transitions the progenitor to a gliogenic state, producing either astrocytes or oligodendrocytes depending on FGF signalling levels. Our results uncover how FOXG1 integrates extrinsic signalling via the FGF pathway to regulate the sequential generation of neurons, astrocytes, and oligodendrocytes in the cerebral cortex.

VAMOS: Middleware for best-effort third-party monitoring - Chalupa, Marek; Mühlböck, Fabian; Muroya Lei, Stefanie; Henzinger, Thomas A (Science of Computer Programming)
As the complexity and criticality of software increase every year, so does the importance of runtime monitoring. Third-party and best-effort monitoring are especially valuable, yet under-explored areas of runtime monitoring. In this context, third-party monitoring means monitoring with a limited knowledge of the monitored software (as it has been developed by a third party). Best-effort monitoring keeps pace with the monitored software at the cost of possibly imprecise verdicts when keeping up with the monitored software would not be feasible. Most existing monitoring frameworks do not support the combination of third-party and best-effort monitoring because they either require the full access to the monitored code or the ability to process all observable events, or both. We present a middleware framework, Vamos, for the runtime monitoring of software. Vamos is explicitly designed to support third-party and best-effort scenarios. The design goals of Vamos are (i) efficiency (tracing events with low overhead), (ii) flexibility (the ability to monitor a variety of different event channels, and to connect to a wide range of monitors), and (iii) ease-of-use. To achieve its goals, Vamos combines aspects of event broker and event recognition systems with aspects of stream processing systems. We implemented a prototype toolchain for Vamos and conducted a set of experiments demonstrating the usability of the scheme. The results indicate that Vamos enables writing useful yet efficient monitors, and simplifies key aspects of setting up a monitoring system from scratch.

Limitation of time promotes cooperation in structured collaboration systems - Zhang, Yichao; Wang, Jiasheng; Wen, Guanghui; Guan, Jihong; Zhou, Shuigeng; Chen, Guanrong; Chatterjee, Krishnendu; Perc, Matjaz (IEEE Transactions on Network Science and Engineering)
Temporal networks are obtained from time-dependent interactions among individuals, whereas the interactions can be emails, phone calls, face-to-face meetings, or work collaboration. In this article, a temporal game framework is established, in which interactions among rational individuals are embedded into two-player games in a time-dependent manner. This allows studying the time-dependent complexity and variability of interactions, and the way they affect prosocial behaviors. Based on this simple mathematical model, it is found that the level of cooperation is promoted when the time of collaboration is equally limited for every individual. This observation is confirmed by a series of systematic human experiments on over 1,400 subjects, forming a foundation for comprehensively describing human temporal interactions in collaboration. The research results reveal an important incentive for human cooperation, leading to a better understanding of a fascinating aspect of human nature in society.

Mesh simplification for unfolding - Bhargava, Manas; Schreck, Camille; Freire, M.; Hugron, P. A.; Lefebvre, S.; Sellán, S.; Bickel, Bernd (Computer Graphics Forum)
We present a computational approach for unfolding 3D shapes isometrically into the plane as a single patch without overlapping triangles. This is a hard, sometimes impossible, problem, which existing methods are forced to soften by allowing for map distortions or multiple patches. Instead, we propose a geometric relaxation of the problem: We modify the input shape until it admits an overlap‐free unfolding. We achieve this by locally displacing vertices and collapsing edges, guided by the unfolding process. We validate our algorithm quantitatively and qualitatively on a large dataset of complex shapes and show its proficiency by fabricating real shapes from paper.
Keywords: fabrication; single patch unfolding; mesh simplification

Structural insights into brassinosteroid export mediated by the Arabidopsis ABC transporter ABCB1 - Wei, H; Zhu, H; Ying, W; Janssens, H; Kvasnica, M; Winne, JM; Gao, Y; Friml, Jiří; Ma, Q; Tan, S; Liu, X; Russinova, E; et al. (Plant Communications)
Brassinosteroids (BRs) are steroidal phytohormones indispensable for plant growth, development, and responses to environmental stresses. The export of bioactive BRs to the apoplast is essential for BR signalling initiation, which requires binding of BR molecule to the extracellular domains of the plasma membrane-localized receptor complex. We have previously shown that the Arabidopsis thaliana ATP-binding cassette (ABC) transporter, ABCB19, functions as a BR exporter, and together with its close homologue, ABCB1, positively regulate BR signalling. Here, we demonstrate that ABCB1 is another BR transporter. The ATP hydrolysis activity of ABCB1 was stimulated by bioactive BRs, and its transport activity was confirmed in proteoliposomes and protoplasts. Structures of ABCB1 in substrate-unbound (apo), brassinolide (BL)-bound, and ATP plus BL-bound states were determined. In the BL-bound structure, BL was bound to the hydrophobic cavity formed by the transmembrane domain, and triggered local conformational changes. Together, our data provide additional insights into the ABC transporter-mediated BR export.

Order-2 Delaunay triangulations optimize angles - Edelsbrunner, Herbert; Garber, Alexey; Saghafian, Morteza (Advances in Mathematics)
The local angle property of the (order-1) Delaunay triangulations of a generic set in R2 asserts that the sum of two angles opposite a common edge is less than π. This paper extends this property to higher order and uses it to generalize two classic properties from order-1 to order-2: (1) among the complete level-2 hypertriangulations of a generic point set in R2, the order-2 Delaunay triangulation lexicographically maximizes the sorted angle vector; (2) among the maximal level-2 hypertriangulations of a generic point set in R2, the order-2 Delaunay triangulation is the only one that has the local angle property. We also use our method of establishing (2) to give a new short proof of the angle vector optimality for the (order-1) Delaunay triangulation. For order-1, both properties have been instrumental in numerous applications of Delaunay triangulations, and we expect that their generalization will make order-2 Delaunay triangulations more attractive to applications as well.

Light-microscopy based connectomic reconstruction of mammalian brain tissue - Danzl, Johann G; Lyudchik, Julia; Kreuzinger, Caroline
The information-processing capability of the brain’s cellular network depends on the physical wiring pattern between neurons and their molecular and functional characteristics. Mapping neurons and resolving their individual synaptic connections can be achieved by volumetric imaging at nanoscale resolution with dense cellular labelling. Light microscopy is uniquely positioned to visualize specific molecules but dense, synapse-level circuit reconstruction by light microscopy has been out of reach due to limitations in resolution, contrast, and volumetric imaging capability. Here we developed light-microscopy based connectomics (LICONN). We integrated specifically engineered hydrogel embedding and expansion with comprehensive deep-learning based segmentation and analysis of connectivity, thus directly incorporating molecular information in synapse-level brain tissue reconstructions. LICONN will allow synapse-level brain tissue phenotyping in biological experiments in a readily adoptable manner.

Influence of surface engineering on the transport properties of lead sulfide nanomaterials - Shu, Haibo; Zhao, Mingjun; Lu, Shaoqing; Wan, Shanhong; Genç, Aziz; Huang, Lulu; Ibáñez, Maria; Lim, Khak Ho; Hong, Min; Liu, Yu (Journal of Colloid and Interface Science)
Lead Sulfide (PbS) has garnered attention as a promising thermoelectric (TE) material due to its natural abundance and cost-effectiveness. However, its practical application is hindered by inherently high lattice thermal conductivity and low electrical conductivity. In this study, we address these challenges by surface functionalization of PbS nanocrystals using Cu2S molecular complexes-based ligand displacement. The molecular complexes facilitate the incorporation of Cu into the PbS matrix and leads to the formation of nanoscale defects, dislocations, and strain fields while optimizing the charge carrier transport. The structural modulations enhance the phonon scattering and lead to a significant reduction in lattice thermal conductivity of 0.60 W m−1K−1 at 867 K in the PbS-Cu2S system. Simultaneously, the Cu incorporation improves electrical conductivity by increasing both carrier concentration and mobility with carefully optimized the content of Cu2S molecular complexes. These synergistic modifications yield a peak figure-of-merit (zT) of 1.05 at 867 K for the PbS-1.0 %Cu2S sample, representing an almost twofold enhancement in TE performance compared to pristine PbS. This work highlights the effectiveness of surface treatment in overcoming the intrinsic limitations of PbS-based materials and presents a promising strategy for the development of high-efficiency TE systems.

Mathematica notebook and Fortran code for 'Effect of assortative mating and sexual selection on polygenic barriers to gene flow' - Surendranadh, Parvathy; Sachdeva, Himani
This file contains the code associated with the manuscript 'Effect of assortative mating and sexual selection on polygenic barriers to gene flow'.

Generalization in multi-objective machine learning - Súkeník, Peter; Lampert, Christoph (Neural Computing and Applications)
Modern machine learning tasks often require considering not just one but multiple objectives. For example, besides the prediction quality, this could be the efficiency, robustness or fairness of the learned models, or any of their combinations. Multi-objective learning offers a natural framework for handling such problems without having to commit to early trade-offs. Surprisingly, statistical learning theory so far offers almost no insight into the generalization properties of multi-objective learning. In this work, we make first steps to fill this gap: We establish foundational generalization bounds for the multi-objective setting as well as generalization and excess bounds for learning with scalarizations. We also provide the first theoretical analysis of the relation between the Pareto-optimal sets of the true objectives and the Pareto-optimal sets of their empirical approximations from training data. In particular, we show a surprising asymmetry: All Pareto-optimal solutions can be approximated by empirically Pareto-optimal ones, but not vice versa.

Watermarkable and zero-knowledge Verifiable Delay Functions from any proof of exponentiation - Hoffmann, Charlotte; Pietrzak, Krzysztof Z (28th IACR International Conference on Practice and Theory of Public-Key Cryptography)
A verifiable delay function VDF(x, T)->(y, π) maps an input x and time parameter T to an output y together with an efficiently verifiable proof π certifying that y was correctly computed. The function runs in T sequential steps, and it should not be possible to compute y much faster than that. The only known practical VDFs use sequential squaring in groups of unknown order as the sequential function, i.e., y = x^2^T. There are two constructions for the proof of exponentiation (PoE) certifying that y = x^2^T, with Wesolowski (Eurocrypt’19) having very short proofs, but they are more expensive to compute and the soundness relies on stronger assumptions than the PoE proposed by Pietrzak (ITCS’19). A recent application of VDFs by Arun, Bonneau and Clark (Asiacrypt’22) are short-lived proofs and signatures, which are proofs and signatures that are only sound for some time t, but after that can be forged by anyone. For this they rely on “watermarkable VDFs”, where the proof embeds a prover chosen watermark. To achieve stronger notions of proofs/signatures with reusable forgeability, they rely on “zero-knowledge VDFs”, where instead of the output y, one just proves knowledge of this output. The existing proposals for watermarkable and zero-knowledge VDFs all build on Wesolowski’s PoE, for the watermarkable VDFs there’s currently no security proof. In this work we give the first constructions that transform any PoEs in hidden order groups into watermarkable VDFs and into zkVDFs, solving an open question by Arun et al. Unlike our watermarkable VDF, the zkVDF (required for reusable forgeability) is not very practical as the number of group elements in the proof is a security parameter. To address this, we introduce the notion of zero-knowledge proofs of sequential work (zkPoSW), a notion that relaxes zkVDFs by not requiring that the output is unique. We show that zkPoSW are sufficient to construct proofs or signatures with reusable forgeability, and construct efficient zkPoSW from any PoE, ultimately achieving short lived proofs and signatures that improve upon Arun et al.’s construction in several dimensions (faster forging times, arguably weaker assumptions). A key idea underlying our constructions is to not directly construct a (watermarked or zk) proof for y = x^2^T, but instead give a (watermarked or zk) proof for the more basic statement that x^l, y^l satisfy x^l = x ^r, y^l = y^r for some r, together with a normal PoE for y^l = (x^l)^2^T.

Evidence of ferroelectric distortions in topological crystalline insulators via transverse thermoelectric measurements - Negi, Pranav; He, Bin; Ukolov, Denis; Horta, Sharona; Maji, Krishnendu; Mao, Ning; Peshcherenko, Nikolai; Yanda, Premakumar; Yao, Mengyu; Dutta, Moinak; Robredo, Iñigo; Iraola, Mikel; et al. (Journal of the American Chemical Society)
The transverse thermoelectric (Nernst) effect is a powerful probe for studying the electronic and structural properties of materials. In this study, we employ transverse thermoelectric measurements to investigate the ferroelectric distortion in the topological crystalline insulator (TCI) Pb0.60Sn0.40Te, a compound derived from PbTe and SnTe, known for their exceptional thermoelectric performance and distinct ferroelectric properties. By leveraging Nernst measurements, we provide direct evidence of ferroelectric distortion in this TCI, corroborated by Shubnikov–de Haas quantum oscillations that confirm the presence of two topologically nontrivial Fermi pockets. Density functional theory calculations show that these pockets originate from the L and T points in the Brillouin zone of the distorted structure within the TCI phase. Raman spectroscopy further identifies a structural phase transition below 50 K, consistent with the quantum oscillation observations. This observation is further substantiated by temperature-dependent synchrotron X-ray pair distribution function analysis and transmission electron microscopy, which confirm the local off-centering of cations at low temperature. These findings underscore the potential of transverse thermoelectric measurements in unveiling ferroelectric distortions and their role in modulating topological quantum states, opening new directions for research into the synergy between ferroelectricity and topological phases.

Token-driven totally asymmetric simple exclusion processes - Kavcic, Bor; Tkačik, Gašper (Physical Review E)
We consider a family of totally asymmetric simple exclusion processes (TASEPs), consisting of particles on a lattice that require binding by a “token” in various physical configurations to advance over the lattice. Using a combination of theory and simulations, we address the following questions: (i) How does token binding kinetics affect the current-density relation on the lattice? (ii) How does this current-density relation depend on the scarcity of tokens? (iii) How do tokens propagate the effects of the locally imposed disorder (such as a slow site) over the entire lattice? (iv) How does a shared pool of tokens couple concurrent TASEPs running on multiple lattices? and (v) How do our results translate to TASEPs with open boundaries that exchange particles with the reservoir? Since real particle motion (including in biological systems that inspired the standard TASEP model, e.g., protein synthesis or movement of molecular motors) is often catalyzed, regulated, actuated, or otherwise mediated, the token-driven TASEP dynamics analyzed in this paper should allow for a better understanding of real systems and enable a closer match between TASEP theory and experimental observations.

Image-based 3D active sample stabilization on the nanometer scale for optical microscopy - Vorlaufer, Jakob; Semenov, Nikolai; Kreuzinger, Caroline; Javoor, Manjunath; Zens, Bettina; Agudelo Duenas, Nathalie; Tavakoli, Mojtaba; Suplata, Marek; Jahr, Wiebke; Lyudchik, Julia; Wartak, Andreas; Schur, Florian Km; et al. (Biophysical Reports)
Super-resolution microscopy often entails long acquisition times of minutes to hours. Since drifts during the acquisition adversely affect data quality, active sample stabilization is commonly used for some of these techniques to reach their full potential. Although drifts in the lateral plane can often be corrected after acquisition, this is not always possible or may come with drawbacks. Therefore, it is appealing to stabilize sample position in three dimensions (3D) during acquisition. Various schemes for active sample stabilization have been demonstrated previously, with some reaching sub-nanometer stability in 3D. Here, we present a scheme for active drift correction that delivers the nanometer-scale 3D stability demanded by state-of-the-art super-resolution techniques and is straightforward to implement compared to previous schemes capable of reaching this level of stabilization precision. Using a refined algorithm that can handle various types of reference structure, without sparse signal peaks being mandatory, we stabilized sample position to ∼1 nm in 3D using objective lenses both with high and low numerical aperture. Our implementation requires only the addition of a simple widefield imaging path and we provide an open-source control software with graphical user interface to facilitate easy adoption of the module. Finally, we demonstrate how this has the potential to enhance data collection for diffraction-limited and super-resolution imaging techniques using single-molecule localization microscopy and cryo-confocal imaging as showcases.

Probing the many-body localized spin-glass phase through quench dynamics - Brighi, Pietro; Ljubotina, Marko; Serbyn, Maksym (Physical Review B)
Eigenstates of quantum many-body systems are often used to define phases of matter in and out of equilibrium; however, experimentally accessing highly excited eigenstates is a challenging task, calling for alternative strategies to dynamically probe nonequilibrium phases. In this work, we characterize the dynamical properties of a disordered spin chain, focusing on the spin-glass regime. Using tensor-network simulations, we observe oscillatory behavior of local expectation values and bipartite entanglement entropy. We explain these oscillations deep in the many-body localized spin-glass regime via a simple theoretical model. From perturbation theory, we predict the timescales up to which our analytical description is valid and confirm it with numerical simulations. Finally, we study the correlation length dynamics, which, after a long-time plateau, resume growing in line with renormalization group (RG) expectations. Our work suggests that RG predictions can be quantitatively tested against numerical simulations and experiments, potentially enabling microscopic descriptions of dynamical phases in large systems.

Singlet-triplet qubits in planar Germanium - Saez Mollejo, Jaime

Stable strategies of direct and indirect reciprocity across all social dilemmas - Hübner, Valentin; Schmid, Laura; Hilbe, Christian; Chatterjee, Krishnendu (PNAS Nexus)
Social dilemmas are collective-action problems where individual interests are at odds with group interests. Such dilemmas occur frequently at all scales of human interactions. When dealing with collective-action problems, people often act reciprocally. They adjust their behavior to match the previous behavior of the recipient. The literature distinguishes two kinds of reciprocity. According to direct reciprocity, individuals react to their immediate experiences with the recipient. They are more likely to cooperate if the recipient previously cooperated with them. According to indirect reciprocity, individuals react to the recipient’s general behavior, irrespectively of whether or not they benefited directly. In practice, the two kinds of reciprocity are often intertwined; people typically base their decisions on both direct experiences and indirect observations. Yet only recently have researchers begun to explore how the two kinds of reciprocity interact. So far, this research only addresses a single type of social dilemma, the donation game, where the effects of individual behaviors are independent. Instead, here we allow for all pairwise social dilemmas. By applying novel techniques to generalize the theory of zero-determinant strategies, we establish an important proof of principle: In all social dilemmas, socially optimal outcomes can be sustained as an equilibrium, using either direct or indirect reciprocity, or arbitrary mixtures thereof. These results neither require games to be repeated infinitely often, nor that individual opinions are synchronized. In this way, we considerably generalize the scope of models of reciprocity, and we build further bridges between the literatures on direct and indirect reciprocity.

Prussian blue analogues as anode materials for battery applications: Complexities and horizons - Palacios Corella, Mario; Echevarría, Igor; Santana Santos, Carla; Schuhmann, Wolfgang; Ventosa, Edgar; Ibáñez, Maria (Chemistry of Materials)
Prussian blue (PB) and Prussian blue analogues (PBAs) are a class of porous materials composed of transition metal cations, cyanide ligands, and alkali metal cations. Their ability to intercalate and deintercalate ions within their framework pores, coupled with the adaptability of their crystal structure to electrochemical changes, underpins their success in battery applications. PBAs with Fe or Co as the active site exhibit high redox potentials (vs SHE) and have been extensively explored as cathode materials, with well-documented chemistry, crystal structures, and electrochemical properties. In contrast, PBAs with Cr or Mn as the active site display lower redox potentials and remain significantly underexplored as anode materials. This gap has led to fewer reported compounds and a less comprehensive understanding of their structural and electrochemical behavior, leaving the field relatively opaque. In this perspective, we comprehensively analyze the challenges involved in producing and employing PBAs with low redox potentials as active battery materials. Conversely, we propose numerous horizons and ask fundamental questions that should pave the way for future research to advance the field.

Superconducting proximity effect in two-dimensional hole gases - Babkin, Serafim; Joecker, Benjamin; Flensberg, Karsten; Serbyn, Maksym; Danon, Jeroen (Physical Review B)
Technology involving hybrid superconductor–semiconductor materials is a promising avenue for engineering quantum devices for information storage, manipulation, and transmission. Proximity-induced superconducting correlations are an essential part of such devices. While the proximity effect in the conduction band of common semiconductors is well understood, its manifestation in confined hole gases, realized for instance in germanium, is an active area of research. Lower-dimensional hole-based systems, particularly in germanium, are emerging as an attractive platform for a variety of solid-state quantum devices, due to their combination of efficient spin and charge control and long coherence times. The recent experimental realization of the proximity effect in germanium thus calls for a theoretical description that is tailored to hole gases. In this work, we propose a simple model to describe proximity-induced superconductivity in two-dimensional hole gases, incorporating both the heavy-hole (HH) and light-hole (LH) bands. We start from the Luttinger–Kohn model, introduce three parameters that characterize hopping across the superconductor–semiconductor interface, and derive explicit intraband and interband effective pairing terms for the HH and LH bands. Unlike previous approaches, our theory provides a quantitative relationship between induced pairings and interface properties. Restricting our general model to an experimentally relevant case where only the HH band crosses the chemical potential, we predict the coexistence of 𝑠-wave and 𝑑-wave singlet pairings, along with triplet-type pairings, and modified Zeeman and Rashba spin–orbit couplings. Our results thus present a starting point for theoretical modeling of quantum devices based on proximitized hole gases, fueling further progress in quantum technology.